Overview of Mycelial Fungi - Lignin Destructors - Afanasevna, Ivanova Lyudmila; Andreevich, FomenkoIvan; Alekseevna, Churmasova Lyudmila; Pavlovna, Kuzmicheva Tatyana (KnE Life Sciences, 2022)
In this work, the following genuses of mycelial fungi, capable of producing ligninolytic enzymes of various actions, were considered:Penicillium, Aspergillus, Fusariumand Altermaria. Fungi of the genus Aspergilluswere capable of producing laccase, manganese peroxidase and lignin peroxidase in the medium. Penicillium mostly produced laccase. Fusariumproduced laccase, aryl alcohol oxidase, manganesedependent peroxidase, manganese-independent peroxidase and lignin peroxidase. Alternariaproduced laccase, lignin peroxidase and manganese peroxidase. The results demonstrated the possibility of using specific substrates in the study of enzyme activity, as well as the influence of some factors introduced into the medium on the synthesis of enzymes. The auxiliary influence of these fungi on the synthesis of ligninolytic enzymes in symbiosis with otherswas considered. Keywords: mycelial fungi, ligninolytic enzymes, Penicillium, Aspergillus, Fusarium, Altermaria